PURIFICATION AND BIOCHEMICAL CHARACTERIZATION OF A T/TN SPECIFIC LECTIN FROM LEPECHINIA BULLATA SEEDS (LAMIACEAE) (2017)
Objective: This study focused on purifying and characterizing a lectin from Lepechinia bullata (L. bullata) seeds, and determining its specificity towards tumour associated carbohydrate-antigens. Methods: Pigments were removed by washing the seeds